CRUDE GLYCEROL FROM BIODIESEL INDUSTRY AS FEEDSTOCK FOR XANTHAN PRODUCTION - Danilović, Nikolina (Journal on Processing and Energy in Agriculture, 2020)
A rapid expansion of the biodiesel industry has created various ecological issues relative to crude glycerol disposal. Xanthan biosynthesis is considered one of the sustainable solutions for minimizing the adverse effects of waste crude glycerol on the environment. The initial phase of xanthan production on crude glycerol entails the screening of producing microorganism. Therefore, the purpose of this study is to examine the possibility of xanthan production on a crude glycerol-based medium using different Xanthomonas campestris strains. The bioprocesses performed were assessed according to the rheology of the media considered, amounts of xanthan produced and conversion degrees of the most important nutrients present. The pseudoplastic behavior of all the media considered, the amounts of xanthan produced (5.22-7.67 g/L) and the degrees of crude glycerol, total nitrogen and phosphorus conversion (34.44-57.61 %, 23.04-30.35 % and 18.20-22.28 %, respectively) suggest that crude glycerol, after  additional bioprocess optimization, can be a suitable raw material for the industrial production of xanthan.
Keywords: waste utilization; crude glycerol; xanthan production; Xanthomonas campestris